Brain Lesion Classification With Effincepresv2: A Hybrid Approach Combining Efficientnetv2 And Inception-Resnetv2 - Goura, Kavita; Harsoor, Anita (Journal of Neonatal Surgery, 2025)
Brain lesion, whether benign or malignant, present significant health risks, making early and precise detection critical for effective treatment. This study explores the use of deep learning for brain lesion classification through MRI imaging, leveraging EfficientNetV2, Inception-ResNetV2, and a hybrid model combining the strengths of both architectures. The dataset comprises MRI scans from patients with gliomas, meningiomas, pituitary tumors, and no-tumors. Pre-processing methods like Channel Standardization, Gaussian blurring, and filtering are used to improve image quality, and data augmentation guarantees that the models will generalize more effectively. Traditional convolutional neural networks (CNNs) are improved by EfficientNetV2 using fused-MBConv layers for increased efficiency, squeeze-and-excitation blocks for adaptive feature scaling, and a progressive training approach that improves accuracy and speed. Inception-ResNetV2, on the other hand, combines ResNet's skip connections with Inception modules for multi-scale feature extraction, enhancing gradient flow and increasing performance on big datasets. The proposed hybrid model EffIncepResV2 maximizes classification accuracy while preserving computational efficiency by combining the efficiency of EfficientNetV2 with the feature extraction capabilities of Inception-ResNetV2.This method is very useful for medical imaging applications since it improves feature extraction and fortifies generalization. The results demonstrate how hybrid deep learning techniques can greatly enhance the classification of brain tumors, ultimately promoting early diagnosis and improved patient outcomes. With an accuracy of 99.94%, precision of 99.65%, recall of 99.89%, F1-score of 99.65, and dice-coefficient of 99%, the results show that EffIncepResV2 performs better than other models. These encouraging findings demonstrate how well EffIncepResV2 can identify brain tumors from MRI pictures, making it a useful diagnostic tool